Inovasi Layanan Samsat Virtu Di Kota Bengkulu - Anwar Fitriyadi; Kahar Hakim; Hardayani, Yorry (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2024)
The innovation of Samsat Virtu Bengkulu City is a breakthrough formed in order to provide public services for motor vehicle tax payment more practically, Samsat Virtu is present as alternative place to pay taxes outside of work hours usual. This study aims to describe and find out the implementation of service innovations formed by the SAMSAT Office through the Samsat Virtu service in Bengkulu City seen from the perception of the community in Borril CS et All with aspects of availability, accessibility, affordability, and acceptance. The research method used is a qualitative descriptive research method. The data collection techniques in this study are observation, interviews, and documentation. In this study, the data analysis techniques used are data reduction, data presentation, and conclusion drawn. The results of the research conducted by the author show that the Samsat Virtu Innovation in Bengkulu City has been implemented and implemented well. However, there are still a few shortcomings, namely in the aspect of availability where there are no vehicle parking barrier signs. In terms of accessibility, it’s well available with regard to schedule information and affordable locations so that it’s easy to find. In terms of affordability, it’s in accordance with the applicable SOP where the imposition of PKB payment fees has been adjusted to the specified calculation. In terms of revenue, it has been carried out so well because the presence of competent officers in providing services so that the taxpayer community feels comfortable and safe in making PKB payments at Samsat Virtu.